Peningkatan Kemampuan Literasi Sains melalui Model Pembelajaran Stem Berbasis ADLX - Sugiyarto, Wahyu (Education & Learning, 2024)
This research aims to improve scientific literacy skills through an ADLX-based STEM learning model. This type of research is Classroom Action Research (PTK). The subjects of this research were class IVA students at SDIT Izzatul Islam Getasan, Semarang Regency. The data collection technique in this research uses test scores and data from observations of the learning process. The data analysis technique used is qualitative and quantitative descriptive analysis. Based on the results of learning process research, the increase in student activity in pre-cycle was 33%, in cycle 1 was 73%, and in cycle 2 was 97%. The increase in learning outcomes in the pre-cycle showed completeness of 53% (16 students), in cycle 1 it was 66%, and in cycle 3 it was 93%. Therefore, it can be concluded that the ADLX-based STEM learning model can improve the scientific literacy skills of class IVA ADIT Izzatul Islam Getasan Semarang Regency students